Immediate risk of cervical intraepithelial neoplasia and diagnostic value of colposcopy among cytology-negative women with oncogenic HPV: a retrospective study - Weichao Dai; Tongfei Wang; Lin Chen; Zhongyuan Qiu; Peifang Chen; Dezhao Chen (BMC, 2024)
Abstract Background Cervical cancer screening results that are negative for cytology but positive for high-risk human papillomavirus (HR-HPV) are not uncommon. One-year follow-up is suggested for patients with no history of HPV positivity under the most recent American Society of Colposcopy and Cervical Pathology (ASCCP) guidelines (2019). The aim of this study was to evaluate the immediate risk of cervical intraepithelial neoplasia (CIN) among cytology-negative patients positive for HR-HPV. The diagnostic accuracy of colposcopy in these patients was investigated. Methods A retrospective study was conducted in patients who were cytology negative but HR-HPV positive and referred for colposcopy from January 2022 to August 2023. Patients were compared in terms of the immediate rate of CIN lesions among the HPV16-positive group, the HPV18-positive group and the non-16/18 HR-HPV-positive group. The distribution of CIN2 + lesions according to age was evaluated. The factors associated with the accuracy of colposcopy were evaluated using univariate and multivariate logistic regression. Results Among the 372 patients, 195 had chronic cervicitis, 131 had CIN1, 37 had CIN2/3, and nine had carcinoma. The immediate rates of CIN2 + lesions and CIN3 + lesions in patients who were not HR-HPV16/18-positive were comparable to those in patients who were HPV16/18-positive (P = 0.699). In addition, among patients diagnosed with CIN2 + lesions, 8 (17.39%) patients were women aged < 30 years. When pathological results were used as a reference, the consistency rate of colposcopy was 61.0% (227/372). Multivariate analyses revealed that age and the type of cervical transformation zone were independent factors affecting the accuracy of colposcopy (P < 0.001). Conclusions In countries with limited resources, immediate colposcopy referral should be recommended for patients who are cytology negative but HR-HPV-positive (including non-16/18 HR-HPV-positive), and cervical cancer screening via cotesting should be suggested for women aged < 30 years. Colposcopy has moderate diagnostic value and can be affected by age and the type of cervical transformation zone.